Does AL amyloidosis have a unique genomic profile? Gene expression profiling meta-analysis and literature overview - Kryukov, Fedor; Kryukova, Elena; Brozova, Lucie; Kufova, Zuzana; Filipova, Jana; Growkova, Katerina; Sevcikova, Tereza; Jarkovsky, Jiri; Hajek, Roman (Gene, 2016)
Immunoglobulin light chain amyloidosis (ALA) is a plasma cell dyscrasia characterized by deposition of amyloid fibrils in various organs and tissues. The current paper is devoted to clarify if ALA has a unique gene expression profile and to its pathogenetic argumentation. The meta-analysis of ALA patients vs. healthy donors, monoclonal gammopathy of undetermined significance, smoldering and multiple myeloma patients' cohorts have revealed molecular signature of ALA consists of 256 genes representing mostly ribosomal proteins and immunoglobulin regions. This signature appears pathogenetically supported and elucidates for the first time the role of ribosome dysfunction in ALA. In summary of our findings with literature overview, we hypothesize that ALA development is associated not only with changes in genes, coding amyloidogenic protein itself, but with post-transcriptional disbalance as well. Based on our data analysis in ALA, ribosome machinery is impaired and the affected link mainly involves translational initiation, elongation and co-translational protein folding.
Keywords: Genes, Immunoglobulin Light Chain; Ribosome; stanovení celkové genové exprese; Amyloidosis; Gene Expression Profiling; Humans; paraproteinemie; amyloidóza; AL amyloidosis; Gene expression profile; lidé; Monoclonal gammapaties; Animals; geny pro lehké řetězce imunoglobulinů; Meta-analysis; Paraproteinemias; zvířata